KUALITAS AUDIT SEBAGAI KATALISATOR PENINGKATAN NILAI PERUSAHAAN PADA PERUSAHAAN BUMN PERIODE 2021-2023: KUALITAS AUDIT SEBAGAI KATALISATOR PENINGKATAN NILAI PERUSAHAAN PADA PERUSAHAAN BUMN PERIODE 2021-2023 - Masruroh, Barokatun; Diana Airawaty (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine the effect of audit quality with audit tenure and KAP reputation indicators on company value in state-owned companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. This study uses a quantitative approach with secondary data. The techniques used in this study are t-test analysis and multiple regression analysis. The research sample consisted of 24 state-owned companies selected using the purposive sampling method based on predetermined criteria. The results of this study indicate that audit tenure and KAP reputation do not have a significant effect on company value. Suggestions from this study such as for further researchers should add other variables that can affect company value, such as financial performance, profitability, or earnings management, etc.